2010
DOI: 10.1097/mot.0b013e3283342780
|View full text |Cite
|
Sign up to set email alerts
|

Antihuman leukocyte antigen antibody-induced autoimmunity: role in chronic rejection

Abstract: Purpose of review-We provide evidence for the role of de novo development of immune responses to self-antigens in the post-transplant period and its possible induction by alloimmunity in the pathogenesis of chronic rejection following lung, heart and kidney transplantation. This review details recent findings for the two distinct yet inter-dependent immune processes in the immunepathogenesis of chronic rejection.Recent findings-The contribution of both humoral and cell mediated allo-immune responses against mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 39 publications
0
54
1
Order By: Relevance
“…A lthough kidney rejection following allotransplantation had been considered to be largely a T-cell mediated phenomenon (1,2), there is growing evidence that B cells and antibodies may play a role in the process (3)(4)(5). In this regard, the nature of the lymphoid cells that infiltrate into the transplanted kidney is of special interest (6,7).…”
Section: Transplantation | Combinatorial Antibody Libraries | Next-gementioning
confidence: 99%
“…A lthough kidney rejection following allotransplantation had been considered to be largely a T-cell mediated phenomenon (1,2), there is growing evidence that B cells and antibodies may play a role in the process (3)(4)(5). In this regard, the nature of the lymphoid cells that infiltrate into the transplanted kidney is of special interest (6,7).…”
Section: Transplantation | Combinatorial Antibody Libraries | Next-gementioning
confidence: 99%
“…While the mechanism of chronic kidney rejection is far from certain, recent studies have suggested that a large set of genes that encode proteins of the innate and adaptive immune system are expressed in the host during rejection (2). Another interesting immunological feature of transplanted kidneys is the appearance of highly organized ectopic B-cell clusters in the transplant (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…High levels of circulating anti-HLA antibodies are associated with poor intermediate and long term survival. Presence of anti-endothelial antibodies is a strong determinant of CAV progression [6,58,[62][63][64][65][66][67][68]. Presence of non-HLA antibodies against cardiac myosin and vimentin has also been associated with pathogenesis of CAV.…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
“…Antibody mediated rejection (AMR) or vascular rejection is associated with anti HLA and antiendothelial antibody formation and has been linked to pathogenesis of CAV [6,[62][63][64]. Anti HLA antibodies can exert effects on allograft through complement dependent and independent pathways.…”
Section: Immunobiology and Pathogenesis Of Coronary Allograft Vasculomentioning
confidence: 99%
See 1 more Smart Citation